Assessing English language needs of electronic engineering students: A case study at polytechnic university of Tirana, Albania - Kanini, Vanina; Bojaxhi, Jola; Brahja, Anjeza; Shehu, Isida; Stojani, Edita (Edelweiss Applied Science and Technology, 2025)
This study explores the English language needs of the five-year engineering students at the Faculty of Information Technology, Polytechnic University of Tirana (PUT). The main objective was to assess whether the current ESP course and the widely used engineering textbook address students’ academic and professional requirements. A structured questionnaire with 17 items was administered to 81 students across electronic, informatics, and telecommunication engineering programs. It was complemented by interviews to gain qualitative insights. Data were analyzed through descriptive statistics and thematic categorization. Key findings reveal a strong recognition of English as essential, yet students reported significant challenges in mastering technical vocabulary, grammar, and listening comprehension. Speaking emerged as the most prioritized skill but also the weakest, while reading was perceived as the most developed due to greater exposure in prior schooling. Results further highlight dissatisfaction with the limited course duration, as students believe the single-semester ESP instruction does not adequately prepare them for academic studies of professional demand. The study concludes that a gap exists between current ESP provision and students’ actual needs. Implications include the necessity for curriculum reform, extending ESP across multiple semesters, and incorporating communicative, task-based approaches. These adjustments would foster higher motivation, improve proficiency, and better align language instruction with engineering students’ future career contexts.